2014
DOI: 10.4322/floram.2014.002
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do Pó de Basalto em Substratos para Mudas de Eucalyptus grandis

Abstract: O pó de rocha basáltica é um resíduo de mineração com potencial para ser reutilizado como um componente de substratos florestais, por conter elementos minerais importantes, como os macronutrientes. O objetivo deste estudo foi avaliar os efeitos do pó de basalto, adicionado em diferentes dosagens a misturas com vermiculita e composto comercial de turfa, no desenvolvimento de mudas de Eucalyptus grandis W. Hill ex Maiden, aos 180 dias após a semeadura. Analisados os dados morfológicos indicadores de qualidade de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
1
9
1
Order By: Relevance
“…The regression equations showed that vermiculite proportions of 84, 78, 74, and 79% in the substrate maximized the final number of leaves in eucalyptus seedlings for irrigation frequencies of 1, 2, 3, and 4 times a day, resulting in values of 10.3, 12.2, 11.3, and 11.3 leaves per plant, respectively (Figure 3). Possibly, vermiculite proportions between 74 and 84% for the substrate constitution provided the best physicochemical properties, essential characteristics for seedling quality according to Ehlers and Arruda (2014), Kratz and Wendling (2016), . Figure 3.…”
Section: Table 1 Analysis Of Variance For the Number Of Definitive Lementioning
confidence: 99%
See 1 more Smart Citation
“…The regression equations showed that vermiculite proportions of 84, 78, 74, and 79% in the substrate maximized the final number of leaves in eucalyptus seedlings for irrigation frequencies of 1, 2, 3, and 4 times a day, resulting in values of 10.3, 12.2, 11.3, and 11.3 leaves per plant, respectively (Figure 3). Possibly, vermiculite proportions between 74 and 84% for the substrate constitution provided the best physicochemical properties, essential characteristics for seedling quality according to Ehlers and Arruda (2014), Kratz and Wendling (2016), . Figure 3.…”
Section: Table 1 Analysis Of Variance For the Number Of Definitive Lementioning
confidence: 99%
“…Success in high-productivity forests depends mainly on seedling quality to produce material suitable for industrial purposes, also involving research with other elements, including substrates (Ehlers & Arruda, 2014;Kratz & Wendling, 2016;Michael, Yu, Wintle, Doronila, & Yuen, 2019). The substrate is the medium in which the roots grow and develop, giving structural support to the seedling shoot and providing water, nutrients, and oxygen necessary for proper plant development (Dutra, Grazziotti, Santana, & Massad, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The production of quality forest seedlings is one of the most important steps in the establishment of planted forests (EHLERS; ARRUDA, 2014;KNAPIK;ANGELO, 2007;PRATES et al, 2012;REIS et al, 2008;WELTER et al, 2011), since the quality of the seedling directly influences the survival and initial growth of plants after planting, impacting the productivity of reforestation (EHLERS; ARRUDA, 2014;PRATES et al, 2012;WOLSCHICK et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the production of quality seedlings it is important that the substrates have characteristics such as biological sterility to avoid contamination by pathogens, good cation exchange capacity associated with good fertility levels, thus providing the nutritional supply for seedling growth, besides having adequate values of pH, electrical conductivity and C/N ratio. In relation to physical aspects, the substrate must be stable and promote an adequate water/air ratio, associated with a level of total porosity that favors both water retention and drainage (ALVES;FREIRE, 2017;EHLERS;ARRUDA, 2014). As these characteristics are hardly found in a single material, sometimes it is necessary to mix more than one component to obtain a desirable combination for the species to be grown.…”
Section: Introductionmentioning
confidence: 99%
“…The states of Paraná and Santa Catarina had the highest concentrations of most elements. In these states, dairy production is located in regions with soils predominantly derived from basalt (Silva and Vaine, 2001), which may explain the higher bioavailability of elements for plant uptake (Costa et al, 2002;Ehlers and Arruda, 2014;Melo et al, 2012;Schmidt et al, 2009). Some elements are not required and can cause toxicity in cattle.…”
mentioning
confidence: 99%